Optical/NIR stellar absorption and emission-line indices from luminous infrared galaxies. Issue 3 (16th April 2019) - Riffel, Rogério; Rodríguez-Ardila, Alberto; Brotherton, Michael S; Peletier, Reynier; Vazdekis, Alexandre; Riffel, Rogemar A; Martins, Lucimara Pires; Bonatto, Charles; Zanon Dametto, Natacha; Dahmer-Hahn, Luis Gabriel; Runnoe, Jessie; Pastoriza, Miriani G; et al.
Abstract: We analyse a set of optical-to-near-infrared long-slit nuclear spectra of 16 infrared-luminous spiral galaxies. All of the studied sources present H2 emission, which reflects the star-forming nature of our sample, and they clearly display H i emission lines in the optical. Their continua contain many strong stellar absorption lines, with the most common features due to $\rm{Ca\, {\small I}}$, $\rm{Ca\, {\small II}}$, $\rm{Fe\, {\small I}}$, $\rm{Na\, {\small I}}$, $\rm{Mg\, {\small I}}$, in addition to prominent absorption bands of TiO, VO, ZrO, CN, and CO. We report a homogeneous set of equivalent width (EW) measurements for 45 indices, from optical to NIR species for the 16 star-forming galaxies as well as for 19 early-type galaxies where we collected the data from the literature. This selected set of emission and absorption-feature measurements can be used to test predictions of the forthcoming generations of stellar population models. We find correlations among the different absorption features and propose here correlations between optical and NIR indices, as well as among different NIR indices, and compare them with model predictions. Although for the optical absorption features the models consistently agree with the observations, the NIR indices are much harder to interpret. For early-type spirals the measurements agree roughly with the models, while for star-forming objects they fail to predict the strengths of these indices.